Association of age at menopause with type 2 diabetes mellitus in postmenopausal women: a systematic review and meta-analysis - Zakerinasab, Faezeh; Al Saraireh, Taif Haiham; Amirbeik, Amirhesam; Zadeh, Rasoul Hossein; Mojeni, Fariba Arbab; Behfar, Qumars (Menopause Review/Przegląd Menopauzalny, 2024)
The onset of menopause usually occurs between the ages of 48 and 52, leading to diverse symptoms in various body systems due to a decrease in estrogen level. Visceral obesity and diminished estrogen level during the menopausal phase are associated with unfavorable metabolic changes, resulting in insulin resistance and increased risk of type 2 diabetes mellitus (T2DM). Owing to the increase in the incidence and prevalence of T2DM in recent decades, it is important to identify predisposing factor such as menopausal age to improve T2DM prevention and management. We searched PubMed, Scopus, and Google Scholar databases to find all studies related to menopause and type 2 diabetes up to August 4, 2023. Studies were reviewed for compliance with the inclusion criteria. Sample size and number of post-menopausal T2DM cases were extracted from studies. Effect sizes and related confidence intervals were calculated for them. The combined analysis of 17 studies demonstrated a significant association between menopausal age and risk of T2DM. The calculated odds ratio (OR) demonstrated that women with menopausal age > 45 had significantly decreased risk of developing T2DM with OR of 0.13 (95% CI: 0.04, 0.22). This effect changed to OR = 0.44 (95% CI: –1.12, 2.00) and 0.21 (95% CI: –1.39, 1.82) for menopausal age > 50 and > 55, respectively. In conclusion, this present meta-analysis emphasizes the importance of the complex relationship between earlier menopausal age and risk of T2DM development.